Use of Decoy Traps to Protect Blueberries from Juvenile European Starlings - Michael R. Conover; Richard A. Dolbeer (Human-Wildlife Interactions, 2017)
Fruit consumption by large flocks of juvenile European starlings (Sturnus vulgaris) is a serious problem for growers of strawberries, grapes, apples, cherries, blueberries, and other small fruit. This study examined if numbers of juvenile European starlings foraging in blueberry orchards could be reduced by catching them in decoy traps and relocating the birds elsewhere. From late July through August of 1989, 620 juvenile starlings were captured in 2 decoy traps at a blueberry orchard in Connecticut. A similar number were caught during the same period in 1990. During these 2 years, numbers of juvenile starlings foraging daily in the orchard dropped from >500 before the traps were opened to1988, when no trapping was conducted, starling numbers at the orchard remained high throughout the summer. Trapped starlings were banded and released unharmed 50–100 km away, and none were seen again at the blueberry orchard. During the 2 years of operation, traps caught only 19 nontarget birds of 6 species; all were released unharmed. Decoy traps were specific for juvenile starlings; no adult starlings were captured. These results indicate that decoy traps can be used in a nonlethal manner to reduce berry losses to flocks of juvenile starlings.